INTENSITAS TERPAAN INFORMASI REGULASI PEMERINTAH TENTANG PERUBAHAN DURASI KARANTINA DI INDONESIA PADA MEDIA ELEKTRONIK TERHADAP MINAT BERWISATA KAUM MILLENIAL KE LUAR NEGERI - Luh Eka Susanti; I Wayan Suadnyana (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2023)
As long as Indonesia was exposed with Covid-19 pandemic, government regulations regarding quarantine changes had adjusted several times. The frequency in which the information is published or reported in electronic media has an influence on the interest of millennials to visit abroad. This study aims to identify the effect of the intensity of exposure to government regulatory information regarding quarantine changes, especially in electronic media, on millennial travel interest abroad. The method used is a questionnaire distributed to 38 people (millennials) with purposive sampling technique. Data analysis using SEM (Structural Equation Modeling) in which the type used is Smart PLS. The relationship between exposure to government regulatory information on changes in quarantine duration (X) and millennial travel interest abroad (Y) is significant with a T-Statistic of 8,214 (> 1.96). The original sample estimate value is positive, which is 0.653 which indicates that the direction of the relationship between exposure to government regulatory information on changes in quarantine duration (X) millennial travel interest abroad (Y) is positive. In other words, there is a positive impact between exposure to information on changes in quarantine and millennials’ interest in traveling abroad.